The mediating role of employee performance on the relationship between delegation of authority and decision making - Alhosani, Adnan; Md Yusoff, Rosman; Ismail, Fadillah; Ur Rehman, Fazal (International Foundation for Research and Development (IFRD), 2018)
The aim of this study is to enhance understanding in the animated extent of delegation authority and its role in decision making. Precisely, the prime objective of this study is to visualize the concept and propose the effects of delegation authority on decision making along with the mediating role of employees’ performance in the Police department at Dubai. Based on an inclusive and systematic literature review of delegation authority, decision making, and employee’s performance, this study will collect data through self-administered questionnaires based survey in a quantitative manner. The collected data will be analyzed through smart partial least square structure equation modelling for validating the model, testing hypothesis, and finding results. This study will highlight some new insights into the relevant knowledge area. Specifically, the results will contribute to enhance the motivational synergy of upper management to include the employees in decision-making process to improve their performance. This study is only limited to the police department of Dubai and future studies can examine the relationship between defined constructs in other service sector and the moderating role of employees’ performance. By integrating delegation authority, decision making, and employee’s performance literature, the prime contributions of this study are the analysis of defined variables in the police department of Dubai with emphasize on new challenges and to boost up the gap of relevant literature.